The monogram murders the new Hercule Poirot mystery - Hannah, Sophie 1971- (Harper, 2015)
Hercule Poirot's quiet supper is interrupted when a young woman confides to him that she is about to be murdered. She is terrified, but begs Poirot not to find and punish her killer. Once she is dead, she insists, justice will have been done. Later that night, Poirot learns that three guests at the fashionable Bloxham Hotel have been murdered, a cufflink placed in each one's mouth. While Poirot struggles to connect the bizarre pieces of the puzzle, the murderer prepares a hotel bedroom for a fourth victim ..
Character created by Agatha Christie. - Originally published: 2014
Keywords: Poirot, Hercule (Fictitious character) / Fiction; Private investigators / Belgium / Fiction; Poirot, Hercule (Fictitious character); Private investigators; Belgium; Belgien